Augmenting Emerging Hospitality Services: A Playful Immersive Experience to Foster Interactions among Locals and Visitors. Issue 2 (20th January 2023) - Prandi, Catia; Nisi, Valentina; Ceccarini, Chiara; Nunes, Nuno
ABSTRACT: As the world becomes increasingly interconnected, digital technologies impact the way humans experience places and spaces in (smart) cities. To some extent, these smart technologies are intertwined with the urban living enabling the augmentation of the city's space and creating new opportunities for playful urban engagement. Moreover, touristic cities are becoming the arena of novel hospitality services, emerging from the widespread use of digital technologies and internet-based platforms. At the same time, visitors look for increasingly "authentic" travel experiences that provide meaningful interactions with locals. New business models, such as those emerging from the sharing economy, flourished in response to these fresh needs and opportunities. However, establishing points of dialogue that bring benefits to both residents and tourists is a complex task that still needs inquiry. Here we extend on previous efforts by proposing a playful immersive experience that focuses on creating an esthetically engaging environment for direct information exchange between locals and visitors. We investigate how technology can mediate and augment such information sharing, engaging tourists in a playful and immersive experience. Results of an experiment with 15 users are analyzed and presented to provide new insights to the HCI community.